Determinants of Club Head Speed in PGA Professional Golfers. Issue 8 (August 2016) - Lewis, Adam L.; Ward, Nick; Bishop, Chris; Maloney, Sean; Turner, Anthony N.
Abstract : Abstract: Turner, AN. Determinants of club head speed in PGA professional golfers. J Strength Cond Res 30(8): 2266–2270, 2016—Club head speed (CHS) has been significantly correlated with golf performance, but only in amateurs. The purpose of this study therefore, was to investigate the relationship between field-based measures of strength and power with CHS in Professional Golfers Association (PGA) professional golfers, and further determine differences between age groups. A correlation design was used to test relationships between squat jump (SJ), seated medicine ball throw (SMBT), rotational medicine ball throw (RMBT), and CHS. Twenty participants volunteered to take part in the study (age, 31.95 ± 8.7 years; height, 182.75 ± 6.88 cm; mass, 90.47 ± 15.6 kg). Intraclass correlation coefficients reported high reliability for performance variables ( r = 0.85–0.95). Significant correlations ( p < 0.01) were found between CHS and SJ ( r = 0.817) and SMBT ( r = 0.706), but not RMBT ( r = 0.572). A stepwise linear regression analysis identified that SJ and SMBT explained 74% of the variance in CHS. When dividing the sample based on age, professionals <30 years ( n = 10; 25.6 ± 2.9 years) displayed significantly ( p ⩽ 0.05) higher CHS and SJ height compared with professionals >30 ( n = 10; 39.7 ± 5.5 years). Correlations to CHS for <30 were significant for SJ ( r = 0.801) and SMBT ( r = 0.643), but nonsignificant for RMBT. Those >30 had significant correlations to CHS not only in SMBT ( r = 0.881) and SJ ( r = 0.729), but also in RMBT ( r = 0.642). The results of this study suggest that SJ and SMBT have the largest contribution to CHS in PGA professional golfers. When comparing age groups, it appears that younger golfers (<30 years) utilize more leg strength whereas older golfers (>30 years) utilize more upper body strength. Results suggest that strength-based leg exercises and power-based chest exercises may improve CHS in professional golfers.